Spoken English as a world language: international and intranational settings - Roberts, Paul (2005)
This thesis sets out to characterise English as a World Language, in contrast with English used in homogeneous, intranational settings. After a brief introduction, the relevant literature is reviewed in two chapters: firstly the concept of an international variety of English is challenged and, following this, there is consideration of current thinking under the headings of English as an International Language and English as Lingua Franca. This preliminary part of the thesis leads to some hypotheses concerning the way in which EWL might be characterised, with particular attention to attitudes among different sorts of speaker.